Bioinspired liver scaffold design criteria. (3rd July 2018) - Mattei, Giorgio; Magliaro, Chiara; Pirone, Andrea; Ahluwalia, Arti
ABSTRACT: Maintaining hepatic functional characteristics in-vitro is considered one of the main challenges in engineering liver tissue. As hepatocytes cultured ex-vivo are deprived of their native extracellular matrix (ECM) milieu, developing scaffolds that mimic the biomechanical and physicochemical properties of the native ECM is thought to be a promising approach for successful tissue engineering and regenerative medicine applications. On the basis that the decellularized liver matrix represents the ideal design template for engineering bioinspired hepatic scaffolds, to derive quantitative descriptors of liver ECM architecture, we characterised decellularised liver matrices in terms of their biochemical, viscoelastic and structural features along with porosity, permeability and wettability. Together, these data provide a unique set of quantitative design criteria which can be used to generate guidelines for fabricating biomaterial scaffolds for liver tissue engineering. As proof-of-concept, we investigated hepatic cell response to substrate viscoelasticity. On collagen hydrogels mimicking decellularised liver mechanics, cells showed superior morphology, higher viability and albumin secretion than on stiffer and less viscous substrates. Although scaffold properties are generally inspired by those of native tissues, our results indicate significant differences between the mechano-structural characteristics of untreated and decellularised hepatic tissue. Therefore, we suggest that design rules - such as mechanical properties and swelling behaviour - for engineering biomimetic scaffolds be re-examined through further studies on substrates matching the features of decellularized liver matrices.